Handbook of marketing scales multi-item measures for marketing and consumer behavior research - Bearden, William O., 1945-; Netemeyer, Richard G., 1956-; Association for Consumer Research (U.S.) (Thousand Oaks, Calif. ; London : SAGE, 1999)
'The Handbook of Marketing Scales' is a compilation of multi-item, self-report measures developed and/or frequently used in consumer behavior and marketing research. Over 150 scales are included in the handbook, many of which were originally published in marketing- and consumer-related journals or conference proceedings.
Published in cooperation with the Association for Consumer Research.
Includes bibliographical references and indexes.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Marketing research; Consumer behavior -- Research